2019
DOI: 10.1055/a-0859-7531
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of FODMAP – reduced diet in irritable bowel syndrome – efficacy, adherence, and body weight course

Abstract: Background FODMAP reduced diet (fermentable oligo-, di-, monosaccharide, and polyols) belongs to the established therapy strategies in irritable bowel syndrome (IBS). However, disadvantages of this diet are significant and may lead to weight loss and insufficient patient adherence. Reports from Germany are not available yet. Material and methods In a prospective study, 93 patients with IBS according to Rom III were investigated. Sixty-three patients were recruited for the study and received standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
1
13
1
2
Order By: Relevance
“…This proportion was even higher than reported earlier 33 and well in line with responses to LFDs which have been recommended by some associations for patients with IBS, 15 although a German study reported low patient adherence. 40 The detection rate of WS among patients with IBS in our study is in good accordance with the proportion of patients described elsewhere. 21 22 However, not only CLE-positive patients, but a large proportion of CLE-negative patients also responded to GFD in our study.…”
Section: Discussionsupporting
confidence: 92%
“…This proportion was even higher than reported earlier 33 and well in line with responses to LFDs which have been recommended by some associations for patients with IBS, 15 although a German study reported low patient adherence. 40 The detection rate of WS among patients with IBS in our study is in good accordance with the proportion of patients described elsewhere. 21 22 However, not only CLE-positive patients, but a large proportion of CLE-negative patients also responded to GFD in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Although patient’s complaints significantly improved, the adherence to an eight-week low FODMAP diet was rather low in another study with 93 patients with IBS; 47% of participants stopped the diet because it was too restrictive. Remarkably, 36% of patients who finished the study showed significant weight loss [85]. Thus, appropriate nutritional advice is necessary to avoid insufficient nutrient intake and unintended weight loss.…”
Section: Low Fodmap Diet For Patients With Irritable Bowel Syndrommentioning
confidence: 99%
“…Among the many factors that have been proposed, intolerance to malabsorptive dietary carbohydrates has become a major cause of IBS, therefore dietary interventions is important[ 27 ]. Many studies have found that low-fermented oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAP) diets significantly improve symptoms[ 28 , 29 ], Zhou et al[ 30 ] fed rats with high doses of FODMAP feed, and observed elevated fecal Gram-negative bacteria and serum lipopolysaccharide levels, as well intestinal inflammation, barrier dysfunction, and visceral allergies response, and these symptoms can be prevented by antibiotics and reversed by a low FODMAP diet; (2) fecal microbiota transplantation (FMT), one of the effective methods for treating IBS, high-dose transplantation or repeated FMT can improve the response rate and intensity of FMT[ 31 ]. Use of FMT shortly after disturbance of the gut microbiota in IBS may improve efficacy[ 32 ], but the current evidence from randomized controlled trials does not suggest that FMT is beneficial for global IBS symptoms[ 33 ].…”
Section: Microbiota-gut-liver-brain Axis and Ibsmentioning
confidence: 99%